Fabrication of SiC@Cu/Cu Composites with the Addition of SiC@Cu Powder by Magnetron Sputtering - Zhang Yunlong; Li Wenbo; Hu Ming; Yi Hongyong; Zhou Wei; Ding Peiling; Tang Lili (International Journal of Photoenergy)
In view of the surface engineering application of electrical contact materials, SiC ceramic particles were introduced into copper matrix composites by the hot-press sintering method for the sake of enhancing the service life of copper matrix electrical contact materials. Magnetron sputtering technology was exploited to form the continuous copper film on the β-SiC powders in order to improve interface wettability between SiC powder and copper matrix. The SiC@Cu powders were treated by magnetron sputtering technology. Then, dynamic deposit behavior was described according to SEM results. The phase constitution, fracture morphology, relative density, porosity, Vickers hardness, and coefficient of thermal expansion of SiC@Cu/Cu composites with different SiC@Cu addition were analyzed in detail. The results showed that SiC@Cu powders with higher fraction in the SiC@Cu/Cu composites would decrease relative density and increase porosity, so it resulted in improvement of Vickers hardness. The addition of SiC@Cu decreased CTE values of the SiC@Cu/Cu composite, especially at high-level fraction SiC@Cu powder.